Dificultades de los estudiantes con el papel específico del campo eléctrico en la Óptica - Brosseau, C. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1993)
This paper deals with the difficulties of the understanding of the specific role of the electric field in Optics among students enrolled in undergraduate physics courses. Wiener's experiment along with symmetry arguments provide the basis for an instructional strategy designed to address this specific difficulty.